The fate of biodegradable polylactic acid microplastics in maize: impacts on cellular ion fluxes and plant growth - Bao, Shijia; Wang, Xi; Zeng, Jianxiong; Yue, Le; Xiao, Zhenggao; Chen, Feiran; Wang, Zhenyu (Frontiers in Plant Science, 2025)
The widespread application of biodegradable microplastics (MPs) in recent years has resulted in a significant increase in their accumulation in the environment, posing potential threats to ecosystems. Thus, it is imperative to evaluate the distribution and transformation of biodegradable MPs in crops due to the utilization of wastewater containing MPs for irrigation and plastic films, which have led to a rising concentration of biodegradable MPs in agricultural soils. The present study analyzed the uptake and transformation of polylactic acid (PLA) MPs in maize. Seed germination and hydroponic experiments were conducted over a period of 5 to 20 days, during which the plants were exposed to PLA MPs at concentrations of 0, 1, 10, and 100 mg L-1. Low concentrations of PLA MPs (1 mg L-1 and 10 mg L-1) significantly enhanced maize seed germination rate by 52.6%, increased plant shoot height by 16.6% and 16.9%, respectively, as well as elevated aboveground biomass dry weight by 133.7% and 53.3%, respectively. Importantly, depolymerization of PLA MPs was observed in the nutrient solution, resulting in the formation of small-sized PLA MPs (< 2 μm). Interestingly, further transformation occurred within the xylem sap and apoplast fluid (after 12 h) with a transformation rate reaching 13.1% and 27.2%, respectively. The enhanced plant growth could be attributed to the increase in dissolved organic carbon resulting from the depolymerization of PLA MPs. Additionally, the transformation of PLA MPs mediated pH and increase in K+ flux (57.2%, 72 h), leading to acidification of the cell wall and subsequent cell expansion. Our findings provide evidence regarding the fate of PLA MPs in plants and their interactions with plants, thereby enhancing our understanding of the potential impacts associated with biodegradable plastics.